Policy Implementation for the Arrangement and Management of MSME Traders in the Coastal Area of Tanjungpinang City - Raja Enkla Kurniadinta Putri Rahmina; Edy Akhyari; Dian Prima Safitri (CV. Era Digital Nusantara, 2026)
This article examines the implementation of policy on the arrangement and management of MSME traders in the coastal area of Tanjungpinang City, with a specific focus on Tepi Laut as a strategic public space, tourism icon, and local economic corridor. The main problem addressed in this study is the absence of an integrated management system that can balance trader livelihoods, spatial order, public comfort, coastal cleanliness, and tourism attractiveness. This study employed a qualitative descriptive approach using primary and secondary data collected through interviews, observation, policy documents, trader data, government reports, and relevant literature. The findings show that policy implementation remains constrained by weak spatial arrangement, fragmented institutional coordination, limited facility support, unclear trader-management mechanisms, and insufficient participatory involvement of MSME traders. The analysis also indicates that MSME trader arrangement should not be understood merely as a matter of control or relocation, but as a governance process that integrates economic empowerment, public-space management, tourism development, and environmental sustainability. The proposed integrated governance model emphasizes four main components: spatial integration, operational integration, participatory integration, and sustainability integration. This model is expected to help local government develop a more orderly, inclusive, competitive, and environmentally responsible system for managing coastal MSME traders. The study concludes that sustainable coastal MSME management in Tanjungpinang requires stronger coordination, clear zoning, trader participation, adequate infrastructure, and continuous monitoring to support both local economic growth and coastal tourism quality.